Identity Building in the Hungarian Reformed Press in the First Half of the 20ᵗʰ Century. The Example of “Református Figyelő” - Réka KISS (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica, 2020)
In my study, I am examining a significant step in the history of the national Reformed press between the two world wars, i.e., the weekly paper Református Figyelő (1928–1933). It is well known that the interwar period which was also called a “religious renaissance” or the “period of the second confessionalization”, is considered to be a period of renewal of religious and ecclesiastical life, deepening of faith and strengthening of denominational identity for each historical church. My study approaches the issue of church press between the two world wars from the perspective of the process of community identity building of the Hungarian Reformed people. On the one hand, I am looking for an answer to how the content of the Reformed identity changed during the century, which were the defining phenomena, historical experiences that decisively influenced the Reformed self-awareness, which were its main problems, the central topics of church public discourse. On the other hand, my research focuses on the role of the ecclesiastical press in shaping public discourses, in building identity, the way its organizational background and internal system of relations developed.